Synaptic proteins associated with cognitive performance and neuropathology in older humans revealed by multiplexed fractionated proteomics - Carlyle, Becky C.; Kandigian, Savannah E.; Kreuzer, Johannes; Das, Sudeshna; Trombetta, Bianca A.; Kuo, Yikai; Bennett, David A.; Schneider, Julie A.; Petyuk, Vladislav A.; Kitchen, Robert R.; Morris, Robert; Nairn, Angus C.; et al. (Neurobiology of aging, 2021)
•Proteomics linked 123 proteins to AD pathology and cognitive performance•Proteins involved in glucose metabolism are altered in cognitive impairment•Frail individuals show pathway dysregulation in absence of AD pathology Alzheimer's disease (AD) is defined by the presence of abundant amyloid-β (Aβ) and tau neuropathology. While this neuropathology is necessary for AD diagnosis, it is not sufficient for causing cognitive impairment. Up to one third of community dwelling older adults harbor intermediate to high levels of AD neuropathology at death yet demonstrate no significant cognitive impairment. Conversely, there are individuals who exhibit dementia with no gross explanatory neuropathology. In prior studies, synapse loss correlated with cognitive impairment. To understand how synaptic composition changes in relation to neuropathology and cognition, multiplexed liquid chromatography mass-spectrometry was used to quantify enriched synaptic proteins from the parietal association cortex of 100 subjects with contrasting levels of AD pathology and cognitive performance. 123 unique proteins were significantly associated with diagnostic category. Functional analysis showed enrichment of serotonin release and oxidative phosphorylation categories in normal (cognitively unimpaired, low neuropathology) and "resilient" (unimpaired despite AD pathology) individuals. In contrast, frail individuals, (low pathology, impaired cognition) showed a metabolic shift towards glycolysis and increased presence of proteasome subunits.